Mobile Solutions and Their Usefulness in Everyday Life - Paiva, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an insight into recent technological trends and innovations in solutions and platforms to improve mobility of visually impaired people. The authors' goal is to help to contribute to the social and societal inclusion of the visually impaired. The book's topics include, but are not limited to, obstacle detection systems, indoor and outdoor navigation, transportation sustainability systems, and hardware/devices to aid visually impaired people. The book has a strong focus on practical applications tested in a real environment. Applications include city halls, municipalities, and companies that must keep up to date with recent trends in platforms, methodologies and technologies to promote urban mobility. Also discuss are broader realms including education, health, electronics, tourism, and transportation. Contributors include a variety of researchers and practitioners around the world. Features practical, tested applications of technological mobilitysolutions for visual impaired people; Presents topics such as obstacle detection systems, urban mobility, smart home services, and ambient assisted living; Includes a number of application examples in education, health, electronics, tourism, and transportation.
Introduction -- Mobile applications for the elderly -- Mobile applications for blind and visually impaired people -- Mobile applications for motor disabled people -- Mobile applications for deaf people -- Mobile applications for children -- Mobile applications for indoor navigation -- Mobile applications applied to public transportation -- Mobile applications to promote independency -- Mobile applications to assure safety at home -- Mobile applications to support disabled people in an educational environment -- Conclusion.
Keywords: Telecommunication; Application software; Electronics; User interfaces (Computer systems).; Human-computer interaction; Communications Engineering, Networks; Computer and Information Systems Applications; Electronics and Microelectronics, Instrumentation; User Interfaces and Human Computer Interaction